Electronic weight scales / Abdul Azim Nur Jaaffar and Fakrul Anuar Saari - Nur Jaaffar, Abdul Azim; Saari, Fakrul Anuar (2004)
Final paper is a part of a course structure for student in their final year. The project is compulsory to us as a final year student for Diploma In Electrical Engineering. The purpose of doing this project is to produce student main power with a very high skill and able to handle a responsibility that been given like this project. We should prepare to deliver a creativity idea and good interpersonal image to our future employee. By doing this project it makes student use all their knowledge, capability, creativity and skills to purpose, create and troubleshoot the project. It is because all of the theory and skills that they have learned from the project will be used in the future. No doubt, everyone is familiar with the kind of scales to be found on Post Office counters. A letter or small parcel is placed on it and the weight and the required postage can be read off it. There is no reason why this cannot be accomplished electronically. Of course, some mechanical ingenuity will be required, as the equipment will include some form of scale or balance mechanism. Moreover, the electronic scales should look similar to the mechanical counterpart. If the latter were not the case, nobody would think of putting a letter on to weight it.